Proactive classical biological control of Lycorma delicatula (Hemiptera: Fulgoridae) in California (U.S.): Host range testing of Anastatus orientalis (Hymenoptera: Eupelmidae) - Gómez Marco, Francesc; Yanega, Douglas; Ruiz, Marta; Hoddle, Mark S. (Frontiers in Insect Science, 2023)
Lycorma delicatula (Hemiptera: Fulgoridae), the spotted lanternfly, native to China, invaded and established in the northeast U.S. in 2014. Since this time, populations have grown and spread rapidly, and invasion bridgeheads have been detected in mid-western states (i.e., Indiana in 2021). This invasive pest presents a significant threat to Californian agriculture. Therefore, a proactive classical biological control program using Anastatus orientalis (Hymenoptera: Eupelmidae), a L. delicatula egg parasitoid native to China, was initiated in anticipation of eventual establishment of L. delicatula in California. In support of this proactive approach, the potential host range of A. orientalis was investigated. Eggs of 34 insect species either native or non-native to the southwestern U.S. were assessed for suitability for parasitism and development of A. orientalis. Of the native species tested, 10, 13, and one were Hemiptera, Lepidoptera, and Mantodea, respectively. Of the non-native species, eight Hemiptera and two Lepidoptera were evaluated. Host range tests conducted in a quarantine facility, exposed individually mated A. orientalis females (Haplotype C) to non-target and target (i.e., L. delicatula) eggs in sequential no-choice and static choice experiments to determine suitability for parasitization and development. Additionally, the sex ratio, fertility, and size of offspring obtained from non-target and target eggs were evaluated. Results of host range testing indicated that A. orientalis is likely polyphagous and can successfully parasitize and develop in host species belonging to at least two different orders (i.e., Hemiptera, Lepidoptera) and seven families (Coreidae, Erebidae, Fulgoridae, Lasiocampidae, Pentatomidae, Saturniidae and Sphingidae). Prospects for use of A. orientalis as a classical biological control agent of L. delicatula in the southwestern U.S. are discussed.